2018
DOI: 10.1186/s12872-018-0877-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between nonalcoholic fatty liver disease and subclinical atherosclerosis: a cross-sectional study on population over 40 years old

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) refers to fatty infiltration of liver in the absence of excessive alcohol abuse. However, the problem that whether NAFLD is correlated with subclinical atherosclerosis assessed by carotid intima-media thickness (CIMT) and brachial-ankle pulse wave velocity (ba-PWV) remains a source of controversy. This can be attributed to the differences in diagnosis methods, population ethnicity, sampling size and bias. This study aimed to further investigate the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Interestingly, the annual rate of CAC progression was significantly higher in participants with ultrasound defined-NAFLD compared to those without NAFLD at baseline and was further increased in subjects with elevated NFS independent of obesity, hypertension, dyslipidemia, and diabetes [ 19 ]. CIMT is also increased in patients with NAFLD (diagnosed by ultrasound or CT) independent of dyslipidemia and hypertension [ 17 , 20 ]. Interestingly, a prospective study showed that increased CIMT and ba-PWV at baseline were associated with a higher risk of developing NAFLD (assessed by ultrasound) and ba-PWV was associated with a higher likelihood of fibrosis as assessed by the NFS, fibrosis-4 (FIB4), and aspartate transaminase (AST) to platelet ratio index (APRI) scores [ 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the annual rate of CAC progression was significantly higher in participants with ultrasound defined-NAFLD compared to those without NAFLD at baseline and was further increased in subjects with elevated NFS independent of obesity, hypertension, dyslipidemia, and diabetes [ 19 ]. CIMT is also increased in patients with NAFLD (diagnosed by ultrasound or CT) independent of dyslipidemia and hypertension [ 17 , 20 ]. Interestingly, a prospective study showed that increased CIMT and ba-PWV at baseline were associated with a higher risk of developing NAFLD (assessed by ultrasound) and ba-PWV was associated with a higher likelihood of fibrosis as assessed by the NFS, fibrosis-4 (FIB4), and aspartate transaminase (AST) to platelet ratio index (APRI) scores [ 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…However, more studies with bona fide histological assessment of NASH and fibrosis are needed to further explore this hypothesis. Interestingly, some studies failed to find an association between ultrasound-defined NAFLD and subclinical atherosclerosis by measuring ba-PWV [ 20 ], carotid to femoral (cf-) PWV [ 22 ], or CAC-defined calcification (higher CAC cutoff >10) [ 23 ] after adjustment for other risk factors.…”
Section: Epidemiologymentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is strongly associated with atherosclerosis (Sookoian and Pirola 2008 ; Zheng et al 2018 ). Peroxisome proliferator-activated receptor γ (PPARγ) was reported to be correlated with NAFLD (Zhu et al 2019b ).…”
Section: Lncrna-h19 and The Pathophysiology Of Atherosclerosismentioning
confidence: 99%
“…Recently Zheng et al (94) performed a cross-sectional study confirming that NAFLD is positively correlated with atherogenic lipid profile and patients enrolled with NAFLD shown carotid intima-media thickness (CIMT) and elevated brachial-ankle pulse wave velocity (ba-PWV) for stiffening.…”
Section: Common Pathogenetic Mechanisms Linking Nafld and Metsmentioning
confidence: 99%